High-Throughput Sequencing-Based Analysis of Rhizosphere and Diazotrophic Bacterial Diversity Among Wild Progenitor and Closely Related Species of Sugarcane (Saccharum spp. Inter-Specific Hybrids) - Malviya, Mukesh Kumar; Li, Chang-Ning; Lakshmanan, Prakash; Solanki, Manoj Kumar; Wang, Zhen; Solanki, Anjali Chandrol; Nong, Qian; Verma, Krishan K.; Singh, Rajesh Kumar; Singh, Pratiksha; Sharma, Anjney; Guo, Dao-Jun; et al. (Frontiers in Plant Science, 2022)
Considering the significant role of genetic background in plant-microbe interactions and that most crop rhizospheric microbial research was focused on cultivars, understanding the diversity of root-associated microbiomes in wild progenitors and closely related crossable species may help breed better cultivars. This study aims to fill a critical knowledge gap on rhizosphere and diazotroph bacterial diversity in the wild progenitors of sugarcane, the essential sugar and the second largest bioenergy crop globally. Using a high-throughput sequencing (HTS) platform, we studied the rhizosphere and diazotroph bacterial community of Saccharum officinarum L. cv. Badila (BRS), S. barberi Jesw. cv Pansahi (PRS), S. robustum (RRS), S. spontaneum (SRS), and S. sinense Roxb.cv Uba (URS) by sequencing their 16S rRNA and nifH genes. HTS results revealed a total of 6202 bacteria-specific operational taxonomic units (OTUs) were identified, that distributed as 107 bacterial groups. Out of that, 31 rhizobacterial families are commonly spread in all five species. With respect to nifH gene, S. barberi and S. spontaneum recorded the highest and lowest number of OTUs, respectively. These results were validated by quantitative PCR analysis of both genes. A total of 1099 OTUs were identified for diazotrophs with a core microbiome of 9 families distributed among all the sugarcane species. The core microbiomes were spread across twenty genera. The increased microbial diversity in the rhizosphere was mainly due to soil physiochemical properties. Most of the genera of rhizobacteria and diazotrophs showed a positive correlation, and few genera negatively correlated with the soil properties. The results showed sizeable rhizospheric diversity exists across progenitors and close relatives. Still, incidentally, the rhizosphere microbial abundance of progenitors of modern sugarcane was at the lower end of the spectrum, indicating the prospect of Saccharum species introgression breeding may further improve nutrient use and disease and stress tolerance of commercial sugarcane. The considerable variation for rhizosphere microbiome seen in Saccharum species also provides a knowledge base and an experimental system for studying the evolution of rhizobacteria-host plant association during crop domestication.